2007
DOI: 10.2170/physiolsci.rp008907
|View full text |Cite
|
Sign up to set email alerts
|

Cell Size and Oxidative Enzyme Activity of Rat Biceps Brachii and Triceps Brachii Muscles

Abstract: Fiber-type distributions, cross-sectional areas, and oxidative enzyme activities of type-identified fibers in the biceps brachii and triceps brachii muscles of 10-week-old male Wistar rats were determined and compared with those in the soleus and plantaris muscles. The soleus and plantaris muscles consisted of two (I and IIA) and three (I, IIA, and IIB) types of fibers, respectively. The deep regions of the biceps brachii and triceps brachii muscles consisted of three types of fibers, while the surface regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 32 publications
1
13
0
Order By: Relevance
“…We found that in resting sedentary rats NR4A3 mRNA and protein expression were higher in the soleus muscle, which consists of [80% type I fibers [24] than in the triceps muscle, which consists of 70% type IIb fibers [25] (Fig. 5).…”
Section: Discussionmentioning
confidence: 81%
“…We found that in resting sedentary rats NR4A3 mRNA and protein expression were higher in the soleus muscle, which consists of [80% type I fibers [24] than in the triceps muscle, which consists of 70% type IIb fibers [25] (Fig. 5).…”
Section: Discussionmentioning
confidence: 81%
“…To determine the effects of training on insulin‐stimulated glucose uptake, 2‐deoxy‐ d ‐[ 3 H]glucose uptake into epitrochlearis muscles was measured in the 7‐week groups in the basal state and in response to increasing doses of insulin. The epitrochlearis muscle was used because its small size makes it suitable for in vitro glucose transport, and because the muscle fiber type composition (type I, 15%; type IIa, 20%; type IIb, 65% ) is similar to that in the deep regions of the triceps (type I, 10%; type IIa, 20%; type IIb, 70% ), the muscle used for other analyses in the current study. Insulin‐stimulated glucose uptake was significantly greater in the trained group than in the sedentary group, with submaximal (300 μU·mL −1 ) and supermaximal (50 mU·mL −1 ) insulin concentrations suggesting improved insulin sensitivity, which is commonly associated with exercise training (Fig.…”
Section: Resultsmentioning
confidence: 95%
“…Some researchers state that the biceps brachii of rats evidence low activity of the oxidative enzymes of the fibres in the surface region of this muscle due to the fact that they do not need to act as antigravitational muscles in this animal (Matsumoto et al, 2007). Others state that larger mammals have a higher percentage of type I fibres due to the need to support their heavier weight (Kawai et al, 2009).…”
Section: Discussionmentioning
confidence: 99%